Lažno pozitivni izvidi ultrazvoka v ginekologiji - Gavrić-Lovrec, Vida (Zdravniški vestnik, 2003)
Background. Ultrasound examination is the most frequenty used and usually the only diagnostic imaging method in gynecology. It gives us informations about characteristics of pelvic organs and their changes and also enables us to form criteria that can be used in their evaluation. False positive results lead to unnecessary invasive diagnostic procedures. Methods. We give a review of possibilities modern ultrasonographic technology provides in evaluation of endometrium in postmenopause, adnexal masses and diagnostics of congenital uterine anomalies. Conclusions. Use of modern ultrasonographic technology reduces the number of false positive results.
Keywords: diagnostika; Endometrij; Endometrium; ginekologija; Maternica, novotvorbe; Ovarian neoplasms; Ovarij, novotvorbe; Ultrasound; ultrazvočna diagnostika; Ultrazvok; Uterine neoplasms